Huddersfield's Roll of Honour 1914-1922 - J. Stansfield, Margaret (University of Huddersfield Press, 2014)
Huddersfield's Roll of Honour 1914-1922 is a detailed account of 3,439 service personnel from Huddersfield who lost their lives during the First World War.